7x-6+3x-5=8x+5-10x-4

Simple and best practice solution for 7x-6+3x-5=8x+5-10x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-6+3x-5=8x+5-10x-4 equation:


Simplifying
7x + -6 + 3x + -5 = 8x + 5 + -10x + -4

Reorder the terms:
-6 + -5 + 7x + 3x = 8x + 5 + -10x + -4

Combine like terms: -6 + -5 = -11
-11 + 7x + 3x = 8x + 5 + -10x + -4

Combine like terms: 7x + 3x = 10x
-11 + 10x = 8x + 5 + -10x + -4

Reorder the terms:
-11 + 10x = 5 + -4 + 8x + -10x

Combine like terms: 5 + -4 = 1
-11 + 10x = 1 + 8x + -10x

Combine like terms: 8x + -10x = -2x
-11 + 10x = 1 + -2x

Solving
-11 + 10x = 1 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
-11 + 10x + 2x = 1 + -2x + 2x

Combine like terms: 10x + 2x = 12x
-11 + 12x = 1 + -2x + 2x

Combine like terms: -2x + 2x = 0
-11 + 12x = 1 + 0
-11 + 12x = 1

Add '11' to each side of the equation.
-11 + 11 + 12x = 1 + 11

Combine like terms: -11 + 11 = 0
0 + 12x = 1 + 11
12x = 1 + 11

Combine like terms: 1 + 11 = 12
12x = 12

Divide each side by '12'.
x = 1

Simplifying
x = 1

See similar equations:

| 148.75=9.25(-6+t) | | 2log^9(x)=log^98+log^9(x-2) | | 27r^2+17n+72=0 | | x+(x+2)=-67 | | log^4[log^4(2x)]=1 | | 0=x^2+26+48 | | log(x)+log(x+5)=log(6x+12) | | 17.625=-2(c+15) | | -5x+6-(7-3x+2x+4)=3 | | 3.67(12-a)=43 | | 3x-5=5x-11 | | x+9=55 | | 12-(4-3x)=21-(12+7x) | | x+7=69 | | y+8=-25 | | 16-(3x+20)=(17-2x)-15 | | 18x-9=9x+3 | | 4p+3g=395 | | -(8-2x)=32 | | 7+25x=20x+10 | | X*0.05=6 | | -(8x-2x)=32 | | 3(x+2)+2x=2(x-7)+2x+5 | | 12y-32=-15 | | 82-(-3)= | | 12y-32=-35 | | -21-(-24)= | | x-24=2x+5 | | 8n^2=24n | | 6x+9=-72-6x | | 24*6x=9-9x | | n^2+w=12 |

Equations solver categories